The Paleozoic formations of the Al Qassim Province in Saudi Arabia as potential sites for geotourism - Kaminski, Michael A.; Garrison, Thomas F.; Yoder, Carl E. (Geotourism/Geoturystyka, 2021)
The Paleozoic formations in the Middle East contain some of the world’s richest petroleum deposits, as they include excellent source and reservoir rocks. The Paleozoic rocks were deposited on the northern continental shelf of the Gondwanan continent at relatively high latitudes, and provide evidence of the Late Ordovician glacial event and associated sea-level changes. They also contain unique fossil remains. The Paleozoic formations exposed in the Al-Qassim province in Saudi Arabia are well-suited to become important sites for geotourism. Because the sedimentary formations are well-exposed and are easily accessible, they have strong capacity for development as tourist destinations. In this paper, we describe eight localities and their significance as potential educational sites for geology and palaeontology, as well as the archeological and economic significance of the Paleozoic formations of Saudi Arabia. The cultural and tourist infrastructure is summarised and a two-day field excursion is proposed.